The effect of subclinical endometritis on reproductive performance in postpartum Bos indicus multiparous beef cows - Oliveira Filho, R. V.; Cooke, R. F.; de Mello, G. A.; Pereira, V. M.; Vasconcelos, J. L.M. [UNESP]; Pohler, K. G. (Elsevier, 2022)
The objective was to investigate the prevalence of subclinical endometritis (SE) in postpartum Bos indicus multiparous beef cows using different polymorphonuclear cells (PMN) threshold ratios, and to evaluate the impacts of SE on their reproductive performance. A total of 689 postpartum Nellore cows (45.2 ± 7.8 days postpartum) were submitted to an estrus synchronization protocol + timed-artificial insemination (TAI). Endometrial cytology samples were collected by cytobrush before the beginning of the protocol. Cows were considered positive for SE if: (PMN) ≥ 3% (PMN3), PMN ≥ 5% (PMN5) and PMN ≥ 7% (PMN7). Pregnancy diagnosis was performed at 30 and 100 d after TAI. The prevalence of cows categorized as positive for SE increased (P < 0.05) as the threshold was lowered (PMN7 = 3.9%; PMN5 = 5.5%; PMN3 = 9.1%). Positive SE cows had similar (P > 0.41) BCS, days postpartum, and expression of estrus at TAI compared with negative SE cows. Positive SE cows had decreased (P = 0.04) pregnancy rates compared to negative SE cows in the PMN5 threshold (26.3 ± 8.7% vs 44.5 ± 4.1%); however, no difference (P > 0.45) was observed between positive and negative SE cows in the PMN3 and PMN7 thresholds. Embryonic mortality between days 30 and 100 was not affected by SE (P > 0.16). In conclusion, the prevalence of SE varies based on the PMN threshold used, whereas SE at the beginning of the TAI protocol decreased the pregnancy rates in postpartum Bos indicus beef cows when the PMN5 was used.
Keywords: Beef cows; Bos indicus; Endometrial cytology; Polymorphonuclear cells; Reproductive performance; Subclinical endometritis